AN ACTION RESEARCH OF USING VOCABULARY WHEEL TO IMPROVE YEAR 2 PUPILS’ VOCABULARY IN THE MALAYSIAN CLASSROOM - Yee Bee Choo; Harzuwani Abd. Wahab (Journal of English Education, 2016)
This research was conducted to find out whether or not the use of Vocabulary Wheel could help to improve pupils’ vocabulary. The data for the study were obtained from four pupils of a primary school in Johor. These pupils were targeted due to their low level of proficiency in English language. Vocabulary Wheel was used as the strategy as the pupils were lack of vocabulary thus affecting their language learning. This is an action research and three data gathering methods such as pupils’ work, teacher’s reflective journal and interview were used. The findings of this study proved that the use of Vocabulary Wheel helped to improve the pupils’ vocabulary as the pupils were able to remember the words longer and know how to use them in the right context. It also helped to encourage their participation and promote their interest. This study proposes the suggestion of using ICT to improve the implementation of the strategy.